The Combination of Hyperuricemia and Elevated High-Sensitivity C-Reactive Protein Increased the Risk of Cardiac Conduction Block - Li N; Cui L; Tse G; Korantzopoulos P; Letsas KP; Bazoukis G; Chen S; Zhang N; Yang X; Liu P; Wu L; Yan GX; et al. (Dove Medical Press, 2024)
Na Li,1 Liufu Cui,1 Gary Tse,2,3 Panagiotis Korantzopoulos,4 Konstantinos P Letsas,5 George Bazoukis,6,7 Shuohua Chen,8 Nan Zhang,2 Xuemei Yang,9 Peipei Liu,10 Lili Wu,11 Gan-Xin Yan,12,13 Gregory Yoke Hong Lip,14,15 Shouling Wu,8 Tong Liu2 1Department of Rheumatology and Immunology, Kailuan General Hospital, Tangshan, Hebei Province, People's Republic of China; 2Tianjin Key Laboratory of Ionic-Molecular Function of Cardiovascular Disease, Department of Cardiology, Tianjin Institute of Cardiology, Second Hospital of Tianjin Medical University, Tianjin, People's Republic of China; 3School of Nursing and Health Studies, Hong Kong Metropolitan University, Hong Kong, People's Republic of China; 4First Department of Cardiology, University of Ioannina Medical School, Ioannina, Greece; 5Arrhythmia Unit, Laboratory of Cardiac Pacing and Electrophysiology, Onassis Cardiac Surgery Center, Athens, Greece; 6Department of Cardiology, Larnaca General Hospital, Larnaca, Cyprus; 7European University Cyprus, Medical School, Nicosia, Cyprus; 8Department of Cardiology, Kailuan General Hospital, Tangshan, Hebei Province, People's Republic of China; 9School of Clinical Medicine, North China University of Science and Technology, Tangshan, Hebei Province, People's Republic of China; 10School of Public Health, North China University of Science and Technology, Tangshan, Hebei Province, People's Republic of China; 11Department of Cardiology, Shanghai Songjiang District Central Hospital, Shanghai, People's Republic of China; 12Lankenau Medical Center and Lankenau Institute for Medical Research, Wynnewood, PA, USA; 13Department of Cardiology, Fuwai Huazhong Hospital, Zhengzhou, Henan Province, People's Republic of China; 14Liverpool Centre for Cardiovascular Sciences, University of Liverpool, Liverpool John Moores University and Liverpool Heart & Chest Hospital, Liverpool, UK; 15Danish Center for Clinical Health Services Research, Department of Clinical Medicine, Aalborg University, Aalborg, DenmarkCorrespondence: Tong Liu, Tianjin Key Laboratory of Ionic-Molecular Function of Cardiovascular Disease, Department of Cardiology, Tianjin Institute of Cardiology, Second Hospital of Tianjin Medical University, Tianjin, People's Republic of China, Email liutong@tmu.edu.cn; liutongdoc@126.com Shouling Wu, Department of Cardiology, Kailuan General Hospital, Tangshan, Hebei Province, People's Republic of China, Email drwusl@163.comObjective: This study aimed to explore the impact of a combination of hyperuricemia (HUA) and excessive high-sensitivity C-reactive protein (hs-CRP) levels on the likelihood of developing cardiac conduction block (CCB). Additionally, it sought to assess whether the influence of uric acid (UA) on CCB is mediated by hs-CRP.Methods: A prospective study was executed utilizing data from the Kailuan cohort, including 81,896 individuals initially free from CCB. The participants were categorized into four groups depending on the existence of HUA and low-grade inflammation (hs-CRP> 3 mg/L). Cox regression analysis was employed to ascertain hazard ratios (HRs) and 95% confidence intervals (CIs) for the risk of incident CCB. A mediation analysis was performed to determine if hs-CRP functioned as a mediator in the connection between UA levels and the incidence of CCB.Results: During a median observation period of 11.8 years, we identified 3160 cases of newly occurring CCB. Compared with the low UA/low CRP group, the combination of HUA and low-grade inflammation elevated the CCB risks (HR:1.56, 95% CI:1.22- 1.99), atrioventricular block (AVB) (HR:1.88, 95% CI:1.27- 2.77), and right bundle branch block (HR:1.47, 95% CI:1.02- 2.12), respectively. Mediation analysis revealed that in the HUA group, compared with the non-HUA group, the risk of CCB elevated by 14.0%, with 10.3% of the increase mediated through hs-CRP.Conclusion: HUA combined with elevated hs-CRP increased the risk of CCB, especially AVB. The connection between UA and the CCB risk was partly mediated by hs-CRP. Keywords: hyperuricemia, inflammation, cardiac conduction block, combined exposure, risk factors, mediation